Side effects of COVID-19 vaccines in the middle eastern population - Murished, Ghida M.; Dandachi, Iman; Aljabr, Waleed (Frontiers in Immunology, 2023)
The COVID-19 pandemic has caused severe worldwide health concerns since the first description of the SARS-COV-2 virus in December 2019. The wide dissemination of this virus, together with the lack of treatment urged vaccine development within a short period of time to elicit protective immunity against COVID-19. Due to their rapid development, potential subsequent side effects of COVID-19 vaccines were overlooked, which might lead to many health concerns. This is especially in patients at a greater risk of harm from COVID-19, such as pregnant women, children, and patients with preexisting chronic diseases. In this review, we provide thus a summary of common to rare side effects of administrated COVID-19 vaccines in the Middle Eastern population. We have found that the distinction between COVID-19 vaccines side effects in terms of frequency and severity is attributed to the differences in study populations, gender, and age. Pain at the injection site, fever, headache, fatigue, and muscle pain were the most common reported side effects. Vaccinated subjects with previous COVID-19 infection exhibited an equivalent neutralizing response after just one dose compared to two doses of vaccine. Consequently, individuals who experienced more side effects had significantly higher antibody levels. This indicates that having better immunity correlates with higher antibody levels leading to a higher frequency of vaccine side effects. Individuals with underlying comorbidities, particularly having known allergies, and those underlying comorbidities such as diabetes, and cancer, might be more prone to post-vaccination side effects. Studies in a high-risk population in the Middle Eastern countries are limited. Future studies should be considered to determine long-term side effects, side effects after booster doses, and side effects differences in case of heterologous and homologous 2 This is a provisional file, not the final typeset article vaccination for better understanding and proper handling of high-risk populations and patients who experience these side effects.